Service Quality and Product Quality Key to Improve Customer Loyalty - Didi Suhendi; Sabihis (Journal of Business and Management Review, 2021)
This research is motivated by the importance of maintaining customer loyalty for the survival of the company. This study aims to determine and analyze customer satisfaction and product quality as keys to increasing customer loyalty. The population of this study were visitors to the Rava Motor workshop for one year, amounting to 3161 customers where the population data was seen from the actual customer entry unit in 2019. Based on Slovin calculations with an error of 10%, a sample of 97 visitors was obtained using incidental sampling technique. The research method used is a survey method with a quantitative approach. Data collection techniques used in this study are questionnaires, observation and interviews. The instrument used has been tested for validity and reliability. The data analysis technique used is the descriptive data analysis technique, multiple correlation and multiple regression. The results of this study indicate that there is a positive effect of service quality on customer loyalty and there is a positive effect of product quality on customer loyalty. In addition, simultaneously that there is a positive effect of service quality and product quality on customer loyalty.